Assessment of Advanced Liver Fibrosis and the Risk for Hepatic Decompensation in Patients With Congestive Hepatopathy. Issue 4 (22nd September 2018) - Lemmer, Alexander; VanWagner, Lisa B.; Ganger, Daniel
Abstract : Congestive hepatopathy (CH) arises from chronically elevated right‐sided heart pressures transmitted to the liver by passive venous congestion. Over time, CH can lead to hepatic bridging fibrosis, decompensated cirrhosis, and hepatocellular carcinoma. Currently, there are no evidence‐based guidelines to direct appropriate screening or management of patients with CH, partly because of the inability of current clinical tools (serum tests, imaging studies, liver stiffness measurements, and liver biopsy) to accurately estimate hepatic fibrosis or the risk for hepatic decompensation. The Model for End‐Stage Liver Disease excluding international normalized ratio (MELD‐XI) score is the only validated serum‐based test to predict clinical outcomes in CH. Noninvasive liver stiffness measurements are proving to be of minimal utility as all patients with CH have elevated values that currently cannot differentiate between congestion and fibrosis. In addition, fibrosis staging by liver biopsy is difficult to standardize because of heterogeneous collagen deposition in CH. Moreover, liver biopsy results have little predictive value for post–heart transplant hepatic outcomes in patients with CH. Evaluating liver nodules and masses is also complicated in CH as the finding of delayed venous washout in nodules is not specific for hepatocellular carcinoma in the background of a congested liver, and these lesions may require biopsy to confirm the diagnosis. The lack of effective clinical tools for predicting liver fibrosis and liver function suggests the need for the development of novel biomarkers in patients with CH to assist in the management of this complicated disease. (Hepatology 2018; 00:000‐000).